Socio-economic information for ILCA's small ruminant programme in the Badeku and Eruwa areas, Oyo state, Nigeria - Okali, C. (International Livestock Centre for Africa, 1979)
Summarizes information on small ruminant production in Nigeria & analyzes the farming system in the Badeku & Eruwa areas of the Oyo State in Nigeria, estimating household size, farm size, crop distribution, degree of involvment in the cash economy, farm income & importance of non-farm income. Relates these parameters to the number of types of small ruminants kept per household so as to estimate the contribution of small ruminants to household meat consumption & total cash sales of agricultural products in the ILCA surveyed areas. Indicates some of the socio-economic constraints set to intensive small ruminant production, considering labour, capital, infrastructure, marketing facilities & cultural preferences.